MANAJEMEN MASALAH PSIKOSOSIOSPIRITUAL PASIEN HIV/AIDS DI KOTA SEMARANG - Yunie Armiyati; Desy Ariana Rahayu; Siti Aisah (Universitas Muhammadiyah Semarang, 2015)
The high incidence of HIV / Aids and deaths due to HIV / Aids provides an overview of how the disease is becoming a serious threat. The problems that need to be anticipated patient to remain optimal quality of life not only handling the problem of physical decline, but also the anticipation and management of psychosocial and spiritual problems. Patients need to take the management of psychosocial and spiritual problems adequately so that quality of life remains optimal. The purpose of this study was to obtain an overview of management experience psychosocial and spiritual problems in patients with HIV / Aids in Semarang. The study used a qualitative design with in-depth interviews and focus group discussions in order to explore the experience of HIV / Aids in the management of psychosociospiritual problems. The results showed largely positive response of HIV / Aids patient in psychosociospiritual aspect by improved coping, spiritual stragegy and social support efforts. Social supports from family, health workers, case managers, peer support groups is a major support system in the management of patient problems. The study recommended that social support from family, health workers, friends, peer support groups and community needs to be improved to prevent and tackle problems of limitation psychosociospiritual problem in HIV / Aids.Keywords : Psychosociospiritual, HIV/ Aids